Lineamientos actuales para la rehabilitación como consecuencia de la DMRE. Revisión bibliográfica (2021)
The purpose of this work is to determine the guidelines for the rehabilitation of AMD patients and update information on which processes and aspects are taken into account to improve the adaptation of the patient with AMD to their new condition and the potentialization of their visual remnant in the daily activities. AMD was found to be a progressive degenerative disorder that affects adults over 50 years of age, this disease is divided into two categories wet and dry and is classified into three stages: early, intermediate and late.